Native Virus Challenge Test Against Vaccinated Chickens With Commercial Active and Inactive IBD Vaccines - Retno Damajanti Soejoedono (Media Veteriner, 1998)
Vaccination trial were conducted on two groups of broiler day-old-chick (DOC) using active and inactive IBD vaccines. First Group was further divided into two groups: one received active IBD vaccination at 7 days of age, and the other received oral vaccination at 7 and 21 days of age, respectively. Both subgroups were then challenged against native IBD isolate, K-5, at 21 days of age. The second Group was arranged similar to the first group, but the second Group received inactive IBD vaccination subcutaneously, at 21 days of age. At 35 days of age, all chickens were challenged against native IBD isolate, K-5. The group which received active vaccine showed pathological change of the bursa, correlated to the bursa/body weight indices less than 0.70 (20 %) and the bursa lesion score (BLS) was 1.56. This pathological change was more obvious after second application of the vaccine. The group which received active and inactive vaccines revealed immune responses with mild lesion in the bursa. This im-munity could not protect the chickens after challenged with K-5 isolate, correlated to the bursa/body weight indices less than 0.70 (100 %) and BLS was 4.0. This results show that K-5 isolate belong to different subtype or variant.